Appraisal of Environmental Related Issues in Social Science Subjects in Secondary Schools in Nigeria - Samuel Olanrewaju Oladapo; Yinka Oluranti Adediran (RIRAI Publisher, 2020)
Environmental conservation and management should be a vital component of our school curriculum as a way of investing in our youth so that they can be capable custodians of our environment for the sake of environmental management and conservation for sustainability. The youth have great potential which can only be ignored at our nation’s peril. Given that the environment is our greatest heritage, all measures including EE education must be taken serious to ensure that our youth have the correct attitude towards the environment since our very survival depends on this, this should be included in the school curriculum at all level. This research work investigates how environmental education can be used as a tool to create awareness and participation of secondary school students in environmental management and conversation. The research design used in this study was descriptive research design of survey type, to examine the curriculum content of secondary school on environmental conservation and management in secondary schools in Ondo State. The population for the study consists of all the secondary school students in Ondo state. Samples of forty-eight (480) students were drawn from ten (10) selected schools by using stratified random sampling technique. Forty-Eight (48) students were drawn from each of the selected schools. The research instrument used for this study was a self-constructed questionnaire for the students of the selected secondary schools. A sect of questionnaire was design, the questionnaire consisted of two sections; A and B: Section A contained the personal data while Section B contained items constructed in four point linkert scale. Findings from the study reveals among others that there are topics related to conservation in social sciences subjects in secondary schools, that majority of teachers are aware of this and also like teaching it. It therefore, recommend that curriculum planners should make topics on environmental issues be made compulsory at all levels of the education.